Immunomodulatory effect of melatonin in SK‐LU‐1 human lung adenocarcinoma cells co‐cultured with peripheral blood mononuclear cells. (23rd July 2014) - Plaimee, P.; Khamphio, M.; Weerapreeyakul, N.; Barusrux, S.; Johns, N. P.
Abstract Objectives The anti‐cancer potential of melatonin has been examined using a variety of experimental approaches. Melatonin immunomodulatory action was evaluated against the lung cancer cell line SK‐LU‐1, in co‐culture with human peripheral blood mononuclear cells (PBMC). Materials and methods Melatonin was tested on the cell line only after 24 h incubation (direct effect), and on the co‐culture system of SK‐LU‐1 and PBMC to investigate any indirect effect. Apoptotic induction of the cancer cells was assessed using annexin V/PI staining with flow cytometric analysis for membrane alteration. Intracellular superoxide anion (O2−) and hydrogen peroxide (H2O2) for intracellular oxidative stress and glutathione (GSH) for intracellular anti‐oxidation were measured with specific fluorescence probes. DNA fractions were measured employing propidium iodide (PI) fluorescence staining. Results High doses of melatonin were directly toxic to SK‐LU‐1 cells, while PBMC‐mediated indirect effect occurred after moderate doses (1 μm). Under co‐culture conditions, increases in apoptotic cell death, increase in oxidative stress by reduction of GSH and cell cycle arrest in G0/G1 in SK‐LU‐1 cells, were observed as the immunomodulatory effect of melatonin. Conclusion Melatonin had indirect effects on lung cancer cells by enhancement of immunomodulatory effects, but further studies of mechanism(s) involved are needed.